(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Introduction: There is tremendous need for Indian data regarding the age of closure of cranial sutures. So, current study was undertaken at S.S.G. Hospital, Vadodara for a period of 1 year. Material & Method: All cases of known age coming for the postmortem examination in which the victim is more than 40 years of age were taken for the study. Both ectocranial and endocranial state were taken into consideration. Results: In female subjects significant in 41-50 years age group significant correlation was found in coronal suture right and left side ectocranially. In male subjects in 51-60 age group sagittal, right and left coronal and right and left lambdoid sutures were correlated ectocranially Statistical Analysis: Spearman rank correlation coefficients, Levene’s test for equality of variances, Student’s t test for equality of means, STATAIC-13 software was used. Conclusion: Suture closure as a predictor of age is very speculative and giving definite age from sutures is very difficult, However range of age can be given with reasonable range after 40 years of age.